Targeting CXCR4 by a selective peptide antagonist modulates tumor microenvironment and microglia reactivity in a human glioblastoma model. Issue 1 (December 2016) - Mercurio, Laura; Ajmone-Cat, Maria; Cecchetti, Serena; Ricci, Alessandro; Bozzuto, Giuseppina; Molinari, Agnese; Manni, Isabella; Pollo, Bianca; Scala, Stefania; Carpinelli, Giulia; Minghetti, Luisa
Abstract Background The CXCL12/CXCR4 pathway regulates tumor cell proliferation, metastasis, angiogenesis and the tumor-microenvironment cross-talk in several solid tumors, including glioblastoma (GBM), the most common and fatal brain cancer. In the present study, we evaluated the effects of peptide R, a new specific CXCR4 antagonist that we recently developed by a ligand-based approach, in an in vitro and in vivo model of GBM. The well-characterized CXCR4 antagonist Plerixafor was also included in the study. Methods The effects of peptide R on CXCR4 expression, cell survival and migration were assessed on the human glioblastoma cell line U87MG exposed to CXCL12, by immunofluorescence and western blotting, MTT assay, flow cytometry and transwell chamber migration assay. Peptide R was then tested in vivo, by using U87MG intracranial xenografts in CD1 nude mice. Peptide R was administered for 23 days since cell implantation and tumor volume was assessed by magnetic resonance imaging (MRI) at 4.7 T. Glioma associated microglia/macrophage (GAMs) polarization (anti-tumor M1 versus pro-tumor M2 phenotypes) and expressions of vascular endothelial growth factor (VEGF) and CD31 were assessed by immunohistochemistry and immunofluorescence. Results We found that peptide R impairs the metabolic activity and cell proliferation of human U87MG cells and stably reduces CXCR4 expression and cell migration in response to CXCL12 in vitro. In the orthotopic U87MG model, peptide R reduced tumor cellularity, promoted M1 features of GAMs and astrogliosis, and hindered intra-tumor vasculature. Conclusions Our findings suggest that targeting CXCR4 by peptide R might represent a novel therapeutic approach against GBM, and contribute to the rationale to further explore in more complex pre-clinical settings the therapeutic potential of peptide R, alone or in combination with standard therapies of GBM.